2019
DOI: 10.1111/cbdd.13571
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of chemical modulation of two‐pore domain potassium channels

Abstract: The K+ ion channels comprising the two‐pore domain (K2P) family have specific biophysical roles in generating the critical regulatory K+ current. Ion flow through K2P channels and, implicitly, channel regulation is mediated by diverse metabolic and physical inputs such as mechanical stimulation, interaction with lipids or endogenous regulators, intra‐ or extracellular pH, and phosphorylation, while their function can be finely tuned by chemical compounds. In the latter category, some drug–channel interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 85 publications
0
14
0
Order By: Relevance
“…A range of physical and chemical signals control K2P function (Enyedi and Czirjak, 2010;Feliciangeli et al, 2014;Renigunta et al, 2015) and various K2P subtypes have emerging roles in a multitude of physiological responses and pathological conditions such as action potential propagation in myelinated axons (Brohawn et al, 2019;Kanda et al, 2019), anesthetic responses (Heurteaux et al, 2004;Lazarenko et al, 2010), microglial surveillance (Madry et al, 2018), sleep duration (Yoshida et al, 2018), pain (Alloui et al, 2006;Devilliers et al, 2013;Vivier et al, 2017), arrythmia (Decher et al, 2017), ischemia (Heurteaux et al, 2004;Laigle et al, 2012;Wu et al, 2013), cardiac fibrosis (Abraham et al, 2018), depression (Heurteaux et al, 2006), migraine (Royal et al, 2019), intraocular pressure regulation (Yarishkin et al, 2018), and pulmonary hypertension (Lambert et al, 2018). Although there have been recent advances in identifying new K2P modulators (Bagriantsev et al, 2013;Lolicato et al, 2017;Pope et al, 2018;Su et al, 2016;Tian et al, 2019;Vivier et al, 2017;Wright et al, 2019) and in defining key structural aspects of K2P channel pharmacology (Dong et al, 2015;Lolicato et al, 2017;Schewe et al, 2019), as is the case with many ion channel classes, pharmacological agents targeting K2Ps remain poorly developed and limit the ability to probe K2P mechanism and biological functions (Sterbuleac, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A range of physical and chemical signals control K2P function (Enyedi and Czirjak, 2010;Feliciangeli et al, 2014;Renigunta et al, 2015) and various K2P subtypes have emerging roles in a multitude of physiological responses and pathological conditions such as action potential propagation in myelinated axons (Brohawn et al, 2019;Kanda et al, 2019), anesthetic responses (Heurteaux et al, 2004;Lazarenko et al, 2010), microglial surveillance (Madry et al, 2018), sleep duration (Yoshida et al, 2018), pain (Alloui et al, 2006;Devilliers et al, 2013;Vivier et al, 2017), arrythmia (Decher et al, 2017), ischemia (Heurteaux et al, 2004;Laigle et al, 2012;Wu et al, 2013), cardiac fibrosis (Abraham et al, 2018), depression (Heurteaux et al, 2006), migraine (Royal et al, 2019), intraocular pressure regulation (Yarishkin et al, 2018), and pulmonary hypertension (Lambert et al, 2018). Although there have been recent advances in identifying new K2P modulators (Bagriantsev et al, 2013;Lolicato et al, 2017;Pope et al, 2018;Su et al, 2016;Tian et al, 2019;Vivier et al, 2017;Wright et al, 2019) and in defining key structural aspects of K2P channel pharmacology (Dong et al, 2015;Lolicato et al, 2017;Schewe et al, 2019), as is the case with many ion channel classes, pharmacological agents targeting K2Ps remain poorly developed and limit the ability to probe K2P mechanism and biological functions (Sterbuleac, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…GI‐530159 was shown to be active on a TREK1 clone lacking the N‐terminus (Loucif et al, 2018). ML67‐33 action requires the C‐type gate near the selectivity filter of the channel (Bagriantsev et al, 2013) and a cryptic binding site for ML335 and ML402 has been identified behind the selectivity filter at the interface between P1 and M4 segments, which allow these compounds to activate the C‐type gate (Lolicato et al, 2017; Şterbuleac, 2019). BL‐1249 also stimulates the C‐type gate but binds to a different site.…”
Section: Discussionmentioning
confidence: 99%
“…developed a virtual screening but in the extracellular cap of K 2P channels to identify inhibitors targeting this site [38]. Nevertheless, due to their pharmacological potential as protein targets in diverse diseases, much evidence has been recently accumulated regarding the molecular characteristics underlying the interactions between different compounds and K 2P channels [39].…”
Section: Discussionmentioning
confidence: 99%